Using research feedback loops to implement a disability case study with Aboriginal and Torres Strait Islander communities and service providers in regional and remote Australia. Issue 1 (2nd January 2023) - Fitts, M. S.; Cullen, J.; Kingston, G.; Wills, E.; Johnson, Y.; Soldatic, K.
ABSTRACT: While there is a well-developed body of literature in the health field that describes processes to implement research, there is a dearth of similar literature in the disability field of research involving complex conditions. Moreover, the development of meaningful and sustainable knowledge translation is now a standard component of the research process. Knowledge users, including community members, service providers, and policy makers now call for evidence-led meaningful activities to occur rapidly. In response, this article presents a case study that explores the needs and priorities of Aboriginal and Torres Strait Islander women in Australia who have experienced a traumatic brain injury due to family violence. Drawing on the work of Indigenous disability scholars such as Gilroy, Avery and others, this article describes the practical and conceptual methods used to transform research to respond to the realities of community concerns and priorities, cultural considerations and complex safety factors. This article offers a unique perspective on how to increase research relevance to knowledge users and enhance the quality of data collection while also overcoming prolonged delays of knowledge translation that can result from the research-production process.